Penerapan Metode Trend Nonlinear untuk Peramalan Jumlah Angkatan Kerja di Kota Bukittinggi - Wahyu Meidi Cendra (EduInovasi: Journal of Basic Educational Studies, 2025)
In the economic growth of a country, the workforce is one of the important aspects in advancing the economy of a country. Bukittinggi City is one of the cities in West Sumatra Province whose workforce has increased every year. various ways to predict the number of workforce, one of which is the nonlinear trend method. Nonlinear trends are used to describe the movement of time series data over a long period of time or over a long period of time and the data used is not continuous. The non-linear trend method is used to solve the workforce problem in Bukittinggi City. Based on the results of linearity detection, the highest value is 0.837 and the scatter plot graph shows the best trend method for analyzing each variable, namely the cubic nonlinear trend method and with the MAPE value of the model, which is 2.08952 because the MAPE value (Mean Absolute Percentage Error) ≤ 10, then the forecast results are very accurate and it can be concluded that the mo del used in forecasting has a very low error rate and based on a comparison of actual data with forecast data that is not much different, it can be concluded that the cubic trend model is right for predicting the number of workforce in Bukittinggi City.